Determination of Chlorophyll-a, Pheophytin-a and β-Carotene Contents of Isolated Photosynthetic Reaction Centre Complexes - Dikio, E.D.; Isabirye, D.A. (Asian Journal of Chemistry, 2011)
Stoichiometric quantities of chlorophyll-a, pheophytin-a and β-carotene extracted from spinach leaves have been determined by analysis of the UV-VIS spectrum of extracted pigments. Two methods of using extinction coefficients of purified pigments at different wavelengths are investigated in this paper. The results indicate that these methods are suitable for the routine determination of pigment stoichiometry.